Modeling and optimization of LCD optical performance - Yakovlev, Dmitry A.; Chigrinov, V. G.; Kwok, Hoi-Sing (John Wiley, 2015)
This book will prove a useful tool for developers of new generations of liquid crystal displays, and for scientists dealing with optical investigation of liquid crystals.